Effect of Workplace Spirituality on Leadership, Job Satisfaction and Organisational Citizenship Behaviour: An Analytical Study in Private Manufacturing Firms - Dubey, Pushkar; Pathak, Dr. Abhishek Kumar; Sahur, Kailash Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Talented and competent employees are considered as assets in the organisations and they need to be retained for the sustainable growth of organisation. This research investigates the effect of workplace spirituality on leadership, job satisfaction and organisational citizenship behaviour among the employees working in the selected private manufacturing firms of Chhattisgarh state. The primary data were collected of 400 employees of selected manufacturing firms working in the selected regions i.e., Raipur, Durg, Raigarh and Korba of Chhattisgarh state. Results indicated that few dimensions of workplace spirituality found positively related with job satisfaction, leadership and organisational citizenship behaviour. Mindfulness, transcendence and sense of community is found positively and significantly linked with job satisfaction; mindfulness and sense of community has also shown significant association with leadership; and transcendence, mindfulness and sense of community predicted significant relationship with organisational citizenship behaviour.